FISCAL PREREQUISITES FOR THE DEVELOPMENT OF GREEN PUBLIC PROCUREMENT IN ZAKARPATTIA REGION, 2021-2025 - Gabriella Loskorikh; Oksana Perchi (State and Regions. Series: Economics and Business, 2026)
The article addresses the development of green public procurement in Zakarpattia Region under changing fiscal conditions, martial law, and growing demand for more efficient use of public resources. The relevance of the topic is determined by the need to combine environmental priorities with local budget capacity, infrastructure modernisation, and long-term expenditure management. The paper discusses the fiscal and institutional prerequisites for applying green criteria in public procurement, distinguishing environmental protection expenditure, environmentally oriented procurement, and verified green procurement. Particular attention is paid to local budget revenue, environmental tax, energy and utility expenditure, life-cycle costing, multi-source financing, and the need for documentary verification and regional management accounting.